Effect of processing treatments on nutritional, anti-nutritional and bioactive characteristics of horse gram (Macrotyloma uniflorum L.) - Rizvi, Qurat Ul Eain Hyder; Kumar, Krishan; Ahmed, Naseer; Chauhan, Divya; Thakur, Priyanka; Jan, Sumaira; Sheikh, Imran (Journal of Postharvest Technology, 2022)
Horse gram (Macrotyloma uniflorum L.) is an important and one of the most nutritious crops that can be utilized as a basic ingredient for the preparation of several foods because of its high nutritional value. Cereal sprouts are supposed to have a better nutritional profile than cereal grains and their products. The present study aimed to explore the changes occurring during the processing treatments such as soaking and germination of horse gram seeds. The effect of processing treatments on nutritional, anti-nutritional, minerals (Fe, Zn, Mn, and Cu), and bioactive components of horse gram was studied at an interval of 12 and 24 h during soaking and 24, 48, and 72 h during the germination treatment. The results revealed that there was a 20.66 and 23.01% rise in protein content during soaking and germination treatments, respectively. The phenolic components were enhanced to 28.49% and antioxidant activity increased by 31.51% respectively after soaking and germination treatments. The anti-nutritional components like phytic acid, trypsin inhibitor, and tannin contents decreased significantly (p≤0.05) to 40.50, 28.57, and 26.79%, respectively after 72 h of germination. The mineral contents of horse gram increased significantly after soaking and germination processing treatments.